The effect of the bio-fertilizer Seek in The content of leaves and roots of nutrientsN,p,K for seedlings of two fig cultivars Ficus carica L - Aola w. Taher; Ihsan J.Ethbeab (University of Thi-Qar Journal of agricultural research, 2021)
This experiment was conducted in the wooden canopy of the Department of Horticulture and Landscaping – College of Agriculture and the Marshes –University of Dhi Qar in the winter season 2020-2021 to study the bio-fertilizer with four concentrations (0, 500, 1000, 1500) g. seedlings and two varieties of fig plant (Black Diyala, Waziri) and the interaction between them. The results showed the superiority of the cultivar Waziri in the traits (the content of the roots of phosphorous and the content of the roots of potassium), which reached(0.4233 % , 1.1983 % The concentration exceeded 1500 g. Shell-1 of the bio-fertilizer in the characteristics of (leaved content of phosphorous, content of leaves of potassium, content of roots of nitrogen, content of roots of phosphorus, content of roots of potassium) reached (0.545 % , 1.545 % , 1.6867 % , 1.5683 % , reached 1.4017 % ) compared to the comparison treatment and the concentration exceeded 1000 gm. Shela-1 in the nitrogen content of leaves 2.002 % The results of the statistical analysis indicate the presence of significant interactions that differ according to the variety and the concentration of the bio-fertilizer.